2014
DOI: 10.1002/ar.22904
|View full text |Cite
|
Sign up to set email alerts
|

Identification of dendritic cells, B cell and T cell subsets in Tasmanian devil lymphoid tissue; evidence for poor immune cell infiltration into devil facial tumors

Abstract: The Tasmanian devil is under threat of extinction due to the transmissible devil facial tumor disease (DFTD). This fatal tumor is an allograft that does not induce an immune response, raising questions about the activity of Tasmanian devil immune cells. T and B cell analysis has been limited by a lack of antibodies, hence the need to produce such reagents. Amino acid sequence analysis revealed that CD4, CD8, IgM, and IgG were closely related to other marsupials. Monoclonal antibodies were produced against CD4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…Previous studies have shown that the Tasmanian devil has the full complement of cells, tissues and organs that are required for a response against DFTD cells (Howson et al, 2014;Kreiss et al, 2008Kreiss et al, , 2009aWoods et al, 2007). Devils are capable of recognising allogeneic skin grafts and can respond to DFTD cells upon vaccination (Kreiss et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the Tasmanian devil has the full complement of cells, tissues and organs that are required for a response against DFTD cells (Howson et al, 2014;Kreiss et al, 2008Kreiss et al, , 2009aWoods et al, 2007). Devils are capable of recognising allogeneic skin grafts and can respond to DFTD cells upon vaccination (Kreiss et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…An absence of the major histocompatibility complex class I (MHC-I) at the cell surface means that tumour cells are not rejected by the Tasmanian devil's immune system and are free to progress into a new tumour at the wound of the recipient (Siddle et al, 2013). Established tumours have poor immune cell infiltration, suggesting that little natural immunity against DFTD exists (Howson et al, 2014;Loh et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…T lymphocytes expressed cell surface CD3, monocytes expressed MHC class II (MHC-II), and B lymphocytes expressed CD79 (34). Identification of lymphocyte subsets required the development of specific mAbs (35). This allowed the identification of CD4 + and CD8 + T cells in the thymus, adult lymph nodes, spleen, BALT, and GALT.…”
Section: Dftd Transmission and Immunology Of Tasmanian Devilsmentioning
confidence: 99%
“…Lymph nodes, spleen, BALT, and GALT contained IgM + and IgG + B cells. Based on the expression of CD1a, CD83, and MHC-II, dendritic cells were identified in the lymph node, spleen, and skin (35). Consequently, Tasmanian devils have the appropriate immune system components for effective immunity.…”
Section: Dftd Transmission and Immunology Of Tasmanian Devilsmentioning
confidence: 99%
“…The immune system does not recognise DFTD cells; immune cell infiltration into the tumour is poor [37] and DFTD-specific antibodies are not produced [38]. As a result, the immune system is not activated and tumour progression continues unimpeded.…”
Section: Emergence Of a New Disease In Tasmanian Devilsmentioning
confidence: 95%